2019
DOI: 10.3390/su11216054
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Recycled Polymer Composites Made from Side-Stream Materials from Different Industries

Abstract: This study examines the mechanical properties of thermoplastic polymer composites manufactured by utilizing different side-stream materials as fillers. Two composites were manufactured from side-stream materials from the construction industry, two were manufactured from side-stream materials from the paper industry, and one was manufactured from side-stream materials from a coating factory. The matrix polymer used in the composites originated from recycling facility. The side-stream materials were used as fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Yet, the impact strength levels obtained in this study align with previously reported values ranging between 0.21-2.70 kJ/m 2 [16]. Importantly, these values fall within the range observed for many traditional materials, particularly foam-based (0.001-5 kJ/m 2 ) and paper-based (2-12 kJ/m 2 ) materials [30,66,[75][76][77]. This underscores the significant potential of the MBC materials for applications in modern interior elements.…”
Section: Impact Strengthsupporting
confidence: 89%
See 2 more Smart Citations
“…Yet, the impact strength levels obtained in this study align with previously reported values ranging between 0.21-2.70 kJ/m 2 [16]. Importantly, these values fall within the range observed for many traditional materials, particularly foam-based (0.001-5 kJ/m 2 ) and paper-based (2-12 kJ/m 2 ) materials [30,66,[75][76][77]. This underscores the significant potential of the MBC materials for applications in modern interior elements.…”
Section: Impact Strengthsupporting
confidence: 89%
“…– is not reported, < is less than, and NB is non-biodegradable during 30 years. * [ 19 , 22 , 24 , 29 , 42 , 55 , 58 , 59 , 60 , 61 , 68 , 75 , 76 , 77 , 83 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the MBCs developed from prior research, it was found that most of the MBCs obtained in this study had increased impact resistance compared to previously reported MBCs [ 28 ]. Additionally, it was discovered that the obtained MBCs exhibited a similar impact resistance to wood particle boards (1–3.5 kJ/m 2 ) [ 85 ] and paperboards (2–4 kJ/m 2 ) [ 86 ], and also had a stronger impact resistance than many types of synthetic foam, like polyimide, polystyrene, polyurethane, phenolic formaldehyde resin foam, and polypropylene foam, with reported values of just around 0.1–1.63 kJ/m 2 [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Addressing challenges and embracing future perspectives can lead to the creation of environmentally friendly, high-performance materials that can replace traditional options in home decorative items or non-load-bearing construction materials along with packaging applications (Figure 7A,B). "-" = not reported [50,52,57,58,74,85,86,[90][91][92][93][94].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%